INTRAOPERATIVE STATE OF THE HEMOCOAGULATION SYSTEM IN PATIENTS WITH OPEN AND ENDOVASCULAR REVASCULARIZATION OF INFRAINGUAL ARTERIAL SEGMENT IN THE PRESENCE OF STENOTIC-OCCLUSIVE PROCESS OF TIBIAL ARTERIES - Venger, I. K.; Kostiv, S. Ya.; Selskyy, B. P.; Orlov, M. P.; Tsiupryk, N. I. (International Journal of Medicine and Medical Research, 2023)
Background. Among all postoperative complications associated with revascularization of atherosclerotic steno-occlusive process of the femoral-distal artery, thrombosis of the reconstruction segment is 6-32%. Objective. Prevention of thrombotic complications through vascular revascularization of the lower extremity by using a pathogenetically reasonable system of postoperative thromboprophylaxis. Methods. The study involved 97 patients with atherosclerotic stenotic-occlusive process of the infrainguinal artery in cases of stenotic-occlusive lesions of the tibial arteries. In order to study the state of the hemocoagulation system on patients, the methods for studying the indicators of coagulation, fibrinolytic and aggregation systems were used. Results. Development of hypercoagulable disorders in the patients who underwent endovascular revascularization of the arterial segment is more intense than in those who underwent open vascular revascularization methods. Hypercoagulation of blood at the intraoperative stage of revascularization takes place primarily due to the activity of factor IIa of the hemocoagulation cascade. Taking into account these circumstances, already at the surgery stage for thromboprophylaxis non-fractionated heparin (NFH) should be prescribed. At the same time for prevention of thromboembolic complications double anti-thrombocyte therapy: clopidogrel, acetylsalicylic acid should be prescribed. Conclusion. Hypercoagulant ability of the blood system, which develops after arterial reconstructive interventions, takes place against the background of low activity of the fibrinolytic blood system, nevertheless a gradual increase in the activity of the aggregation capacity of the blood. Development of hypercoagulable disorders at the intraoperative stage of surgery in the patients with endovascular methods of arterial reconstructions is more intense than in those treated with open methods of arterial revascularization. Taking into account these circumstances, already at the surgery stage for thromboprophylaxis an anticoagulant should be prescribed that has a targeted effect on factor IIa of the hemocoagulant cascade with simultaneous prevention of thromboembolic complications – double anti-thrombocyte therapy.